Defective vascular signaling & prospective therapeutic targets in brain arteriovenous malformations. (June 2019) - Winkler, Ethan A.; Lu, Alex Y.; Raygor, Kunal P.; Linzey, Joseph R.; Jonzzon, Soren; Lien, Brian V.; Rutledge, W. Caleb; Abla, Adib A.
Abstract: The neurovascular unit is composed of endothelial cells, vascular smooth muscle cells, pericytes, astrocytes and neurons. Through tightly regulated multi-directional cell signaling, the neurovascular unit is responsible for the numerous functionalities of the cerebrovasculature – including the regulation of molecular and cellular transport across the blood-brain barrier, angiogenesis, blood flow responses to brain activation and neuroinflammation. Historically, the study of the brain vasculature focused on endothelial cells; however, recent work has demonstrated that pericytes and vascular smooth muscle cells – collectively known as mural cells – play critical roles in many of these functions. Given this emerging data, a more complete mechanistic understanding of the cellular basis of brain vascular malformations is needed. In this review, we examine the integrated functions and signaling within the neurovascular unit necessary for normal cerebrovascular structure and function. We then describe the role of aberrant cell signaling within the neurovascular unit in brain arteriovenous malformations and identify how these pathways may be targeted therapeutically to eradicate or stabilize these lesions. Highlights: Normal cerebrovascular function requires coordination of multiple cell types. Brain AVMs are high flow arterial-venous shunts which may rupture. Brain AVMs arise from abnormalities in TGF-β, VEGF, NOTCH or other signaling pathways. New therapies are being developed to target disrupted signaling pathways in brain AVMs.